Study of the Influence of Ultrasonic Waves on Electro-physical Characteristics of Radiation Receivers - Abdumalik Gaybullaevich, Gaibov; Kutbiddin Iloviddinovich, Vakhobov; Marguba Sunnatullaevna, Mipkomilova; Utkir Ergashevich, Juraev; Barno Vokhidovna, Ibragimova (International Journal of Psychosocial Rehabilitation, 2020)
The physical processes of capture and ejection of charge carriers in Si-n-p radiation detectors, affecting their electro-physical characteristics (current-voltage), are investigated. It was shown that after ultrasonic treatment of Si detectors, the height of the potential barrier of p-n junctions formed by the presence of local clusters of impurity atoms decreased.